1971
DOI: 10.1084/jem.134.3.642
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the Localized and Generalized Shwartzman Reactions by an Anticomplementary Agent, Cobra Venom Factor

Abstract: The Shwartzman phenomenon may be defined as the pathologic manifestation of disseminated intravascular coagulation with widespread hemorrhagic necrotic lesions and bilateral renal cortical necrosis induced by the administration of two spaced injections of endotoxic lipopolysaccharide (LPS).I Results of previous investigations indicate that the platelet-LPS interaction with subsequent platelet adherence and release of its contents is primarily responsible for the pathologic alterations of the coagulation system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 22 publications
(17 reference statements)
2
25
0
Order By: Relevance
“…A fall in hemolytic complement titers has been observed in rabbits and dogs after intravenously administered endotoxin (13)(14)(15)(16). The present studies demonstrated the same phenomenon in monkeys, but the rapidity of the decrease was striking.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…A fall in hemolytic complement titers has been observed in rabbits and dogs after intravenously administered endotoxin (13)(14)(15)(16). The present studies demonstrated the same phenomenon in monkeys, but the rapidity of the decrease was striking.…”
Section: Resultssupporting
confidence: 63%
“…CoF treatment had no influence on the endotoxin-induced neutropenia of the Shwartzman reaction in rabbits but events during the first 4 h postinjection were not reported (16). The accumulation of neutrophils in inflammatory exudates following i.p endotoxin administration was markedly retarded in C5-deficient mice (55).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, it was shown that the complement system plays a role in DIC [13,14], FUT-175 has potent inhibitory effects on C lr and Cl esterase and complementmediated hemolysis by the classical and al ternative pathways [1,15]. Although this an ticomplement activity might contribute in some way to reduce the extent of changes of the coagulation parameters caused by DIC, the exact mechanism requires further investi gation.…”
Section: Discussionmentioning
confidence: 99%
“…Albino rabbits were injected intravenously with 160 anticomplementary units of CVF [2], Blood samples were obtained from the rabbits at different time intervals for a total period of 15 days. Total, Cl, and C5-9 hemolytic complement component activities were assayed and presented as the percentage of original activity ( fig.…”
Section: In Vivo Experimentsmentioning
confidence: 99%